The effect of lactic acid fermentation of Bactronophorus thoracites on antimicrobial activity against rice pathogens - Jamal, Siti Norazura; Muhialdin, Belal J.; Saidi, Noor Baity; Lai, Kok Song; Yusof, Mohd Termizi; Lamasudin, Dhilia Udie (University Sains Malaysia, 2022)
Aims: Leaf blight disease caused by Pantoea spp. reduces rice yields in numerous nations. However, the exact strategy to combat Pantoea spp. has yet to be determined. Bactronophorus thoracites is a promising source of natural antimicrobial agents due to their potential as a substrate to generate peptides with high antimicrobial activity. This study determined the effects of lactic acid fermentation using Lactobacillus casei ATCC334 as a starter culture on antimicrobial activity against rice pathogens, proximate composition, and amino acid profiles from B. thoracites crude extract. Methodology and results: Bactronophorus thoracites was washed and deshelled to collect the flesh and homogenised at 4 °C before freeze-drying. The freeze-dried samples were fermented with L. casei for 4 to 8 days at 37 °C. The antimicrobial activity, MIC and MBC were determined using a spectrometer. The fermented protein was subjected to proximate and amino acid analyses. The antimicrobial activity of fermented B. thoracites protein (FBTP) was significantly (p<0.05) decreased with the increased fermentation days (from 4 to 8 days). The antimicrobial activity was also increased when the glucose concentration increased from 2% to 3%. However, raising the glucose concentration to 4% decreased the antimicrobial activity. The antimicrobial activity was significantly (p<0.05) increased when the substratewater (S/W) ratio increased from 0.84% to 0.96%. The FBTP (4 days, 3% glucose concentration and 0.96% S/W ratio) showed high antimicrobial activity against Pantoea ananatis and P. stewartii. The MIC and MBC values for FBTP were 500 µg/mL and 250 µg/mL against P. ananatis and P. stewartii. The zones of inhibition value for FBTP were 16.0 ± 0.5 mm (1000 µg/mL) and 9.33 ± 0.57 mm (500 µg/mL) for P. ananatis, and 11.7 ± 0.61 mm (1000 µg/mL), 9.33 ± 0.58 mm (500 µg/mL) and 7.17 ± 0.77 mm (250 µg/mL) for P. stewartii. The proximate composition and amino acid profiles of the freeze-dried protein hydrolysate powder were characterised. FBTP produced a higher value of protein (61.56%) and ash (32.38%) and a lower value of total fat (0.273%) and carbohydrates (6.27%) than the B. thoracites crude extract. Total amino acid content was 39.480 g/100 g in B. thoracites crude extract and 155.442 g/100 g in FBTP. The essential amino acid glutamine was the most abundant in B. thoracites crude extract and methionine in FBTP. Conclusion, significance and impact of study: This study showed that lactic acid fermentation could produce FBTP using L. casei with improved functional characteristics and as a source of a natural antimicrobial agent against rice pathogens.